Inhibition of viroid infection by antisense RNA expression in transgenic plants - Matousek, J; Schröder, A R; Trnĕná, L; Reimers, M; Baumstark, T; Dĕdic, P; Vlasák, J; Becker, I; Kreuzaler, F; Fladung, M (Biological chemistry Hoppe-Seyler, 1994)
Complex formation between different antisense RNAs directed against either plus-strand or minus-strand sequences of the potato spindle tuber viroid (PSTVd) was studied using temperature-gradient gel electrophoresis and immunochemical detection with an antibody specific for double-stranded RNA. Short minus-strand sequences were directed against the upper central conserved region (UCCR) of plus-strand viroid replication intermediates, a plus-strand corresponding to the left half of the rod-like secondary structure (VL+) against minus-strand replication intermediates. It was shown that antisense RNA forms complexes with the corresponding target RNA only with low yield during incubation at low (physiological) temperatures but with high yield during in vitro transcription of the target RNA when the antisense RNA is already present in the solution. The antisense RNA sequences were integrated into Solanum tuberosum L. by Agrobacterium tumefaciens transformation. Antisense RNA expression in vivo was analyzed by Northern analysis. Infection tests were performed using the transgenic potato lines in order to evaluate their degree of resistance against PSTVd infection. Although some lines showed a significant inhibition of viroid accumulation, a high variability of viroid infection in different transgenic potato lines was obtained. Since strongly infected plants were observed in all transgenic lines 6 to 8 weeks post inoculation, a threshold concentration of viroid, overcoming the antisense effect has to be assumed. When the rate of viroid accumulation was tested using agroinfection assays on leaf discs, a stronger antisense effect could be achieved.
Keywords: genetická transkripce; dvouvláknová RNA; RNA virová; Transformation, Genetic; transformace genetická; sekvence nukleotidů; Molecular Sequence Data; Solanum tuberosum; Transcription, Genetic; molekulární sekvence - údaje; geneticky modifikované rostliny; viroidy; Antibodies, Monoclonal; antisense RNA; Base Sequence; Plants, Genetically Modified; RNA, Antisense; Viroids; RNA, Double-Stranded; monoklonální protilátky; RNA, Viral; Agrobacterium tumefaciens